The Effect of Volunteer Management on Intention to Continue Serving as a Volunteer with Organizational Commitment as a Mediator Among Indonesian Red Cross (PMI) Volunteers - Yolanda Agustianeta; Wa Ode Zusnita Muizu; Yunizar Yunizar (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2026)
Indonesia is a country with a high frequency of disaster occurrences. The role of humanitarian volunteers in disaster management activities was very important. However, managing volunteers remained a major challenge for non-profit organizations such as the Indonesian Red Cross (PMI). This study aimed to examine how volunteer management affected volunteers’ intention to continue, with organizational commitment as a mediating variable among PMI KSR volunteers in West Java. This study used a quantitative approach with an explanatory method. Data were collected through a questionnaire survey. The data were analyzed using Structural Equation Modeling (SEM). The results showed that volunteer management had a positive and significant effect on organizational commitment, while organizational commitment had a positive and significant effect on intention to continue as a volunteer. In contrast, volunteer management showed a negative direct effect on intention to continue as a volunteer. In addition, organizational commitment was proven to significantly mediate the relationship between volunteer management and intention to continue as a volunteer, indicating the presence of a competitive mediation effect. These findings emphasized the importance of strengthening organizational commitment as a key mechanism to enhance volunteer sustainability and improve the effectiveness of volunteer management practices in humanitarian organizations.